ANALYSIS OF ASTUE AT OJSC «BSW – MANAGEMENT COMPANY OF «BMC» HOLDING» ON THE BASIS OF SINIS - S. V. Demyanov (Литьë и металлургия)
An automated system of technical calculation of energy resources intended to account for the of power means: delivery water, steam, natural gas, etc. is considered.